Analysis of Container Lashing System Optimization Based on Technical, Economic, and Environmental Aspects in an Effort to Improve Work Safety and Cargo Stability on KM. Tanto Handal - Farisi, Mohammad Noval; Purwanto, F.X. Adi (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2026)
Navigational safety is a crucial aspect of ship operations, where the stability and security of cargo play a significant role. MV Tanto Handal, as a container vessel, requires proper lashing procedures to prevent cargo shifting that may lead to accidents. This study focuses on optimizing container lashing to improve cargo stability and navigational safety. The optimization process involves evaluating lashing techniques, equipment feasibility, safety procedures, and inspections conducted during the voyage. Factors such as inadequate equipment, weather conditions, and human error are identified as major causes of ineffective lashing. The findings emphasize the importance of enhancing crew training and improving lashing procedures to achieve safer and more efficient operations.